Use of Misoprostol in Pregnancy- A Review Article - Kulsum, Syeda Ummay; Khatun, Sabera; Tabib, SM Shahnawaz Bin (Medicine Today, 2012)
Prostaglandins are the pharmacological agents used for induction of labour and augmentation of labour. Prostaglandin E2 gel is used for cervical ripening and induction of labour. These are however, costly and need to be stored in a refrigerator at a temperature of 2 - 8°C, half life 18 months. The Tablet form of prostaglandin E2 is not available in Bangladesh. Misoprostol, a synthetic prostaglandin (PG) E1 analogue is used orally for the treatment of gastric and duodenal ulcer and used as a cytoprotective agent. It was first used for labour induction in 1987. Prostaglandin can be used in several gynaecological and obstetric conditions. It can be given through several routes. This article will elaborately delinate the role of misoprostol, a prostaglandin in obstetrics and gynaecological conditions. Medicine Today 2010 Volume 22 Number 02 Page 94-98 DOI: http://dx.doi.org/10.3329/medtoday.v22i2.12443